2017
DOI: 10.1016/j.carres.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of the capsular polysaccharide expressed by Burkholderia thailandensis strain E555:: wbiI (pKnock-KmR) and assessment of the significance of the 2-O-acetyl group in immune protection

Abstract: Burkholderia pseudomallei and its close relative B. mallei are human pathogens that are classified as Tier 1 bio-threat agents. Both organisms have previously been shown to constitutively produce a capsular polysaccharide (CPS) that is both a virulence determinant and protective antigen. Extraction and purification of CPS for use as a potential vaccine candidate requires containment level 3 laboratories which is expensive and time-consuming. B. thailandensis strain E555 is closely related to B. pseudomallei an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…pseudomallei are highly similar (94.4% and 96% nucleotide and protein similarity, respectively) [ 17 ], and nuclear magnetic resonance spectroscopy has shown that the structures of CPS produced by E555 and that of B . pseudomallei are identical [ 23 ]. Previously, BTCV has been isolated from human blood in the USA in 2003 (strain CDC3015869; ST101, USA [ 24 ]) and from environmental samples in Cambodia in 2010 (strain E555; ST696), Gabon in 2013 (strain D50; ST1126 [ 25 ]) and Laos in 2015 (strain ST_10; ST696 [ 26 ]).…”
Section: Introductionmentioning
confidence: 99%
“…pseudomallei are highly similar (94.4% and 96% nucleotide and protein similarity, respectively) [ 17 ], and nuclear magnetic resonance spectroscopy has shown that the structures of CPS produced by E555 and that of B . pseudomallei are identical [ 23 ]. Previously, BTCV has been isolated from human blood in the USA in 2003 (strain CDC3015869; ST101, USA [ 24 ]) and from environmental samples in Cambodia in 2010 (strain E555; ST696), Gabon in 2013 (strain D50; ST1126 [ 25 ]) and Laos in 2015 (strain ST_10; ST696 [ 26 ]).…”
Section: Introductionmentioning
confidence: 99%
“…To construct the glycoconjugates, extracted CPS from B. thailandensis strain E555 [32] was activated with sodium periodate and covalently linked to Crm197 or GD3K6D3G TCVLPs via reductive amination. Conjugation was confirmed by SDS PAGE and agarose gel with Coomassie staining (Figure 2A and 2B, respectively), which confirms the shift in molecular weight from unconjugated carrier protein to conjugate; and immunogold staining TEM (Figure 3A and 3B), which confirmed presence of CPS immunogenic epitope integrity through binding of an anti-CPS monoclonal.…”
Section: Resultsmentioning
confidence: 99%
“…The O-PS deficient mutant of B. thailandensis E555 harbouring a kanamycin-resistance marked, in-frame deletion of its wbiI gene ( B. thailandensis E555 :: wbiI (p-Knock KmR)) [31] was grown in 2 L of LB broth overnight at 37°C with shaking. The CPS was extracted via a modified hot-phenol method and purified as described previously [32].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, strong antibody responses were observed following vaccination with OMVs particularly towards the LPS O-antigen and CPS. Other works have shown high IgG and IgM responses are generated by mice vaccinated with the CPS from B. thailandensis E555 [ 30 ]. The higher immunogenicity of lipid A in B. thailandensis LPS may contribute to better memory responses by inducing stronger local inflammation that attracts more antigen presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptions to the rule have been discovered, where environmental isolates of B. thailandensis strains with a capsule have been identified but remain highly attenuated [ 29 ]. A recent paper has demonstrated that CPS isolated from one such strain, ( B. thailandensis strain E555) can afford significant protection to mice challenged intraperitoneally with B. pseudomallei K96243 [ 30 ]. For the most part, close genetic and antigenic homology means that material from any of the three species can be used to vaccinate against glanders or melioidosis but does not discount the possibility that species-specific antigens might be absent [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%